The role of social media in reducing stigma and discrimination. (June 2015) - Betton, Victoria; Borschmann, Rohan; Docherty, Mary; Coleman, Stephen; Brown, Mark; Henderson, Claire
Summary: This editorial explores the implications of social media practices whereby people with mental health problems share their experiences in online public spaces and challenge mental health stigma. Social media enable individuals to bring personal experience into the public domain with the potential to affect public attitudes and mainstream media. We draw tentative conclusions regarding the use of social media by campaigning organisations.